EFFECT OF WORK ENVIRONMENT ON LECTURER PERFORMANCE MEDIATED BY WORK MOTIVATION AND JOB SATISFACTION - Narasuci, Win; Setiawan, Margono; Noermijati, Noermijati (Jurnal Aplikasi Manajemen, 2018)
This research aims to examine and analyze the direct effect of the work environment on lecturer performance and indirect effect of work environment on lecturer performance through work motivation and job satisfaction in State Polytechnic of Malang. The population of this research is all lecturers State Polytechnic of Malang with civil servant status (PNS) amounted to 314 people with 256 respondents. Data were obtained by using questionnaire. Partial Least Square (PLS) is used to analyze and test the hypothesis that followed by online Sobel test to test the variables of work motivation and job satisfaction as mediation. This study shows that there is a positive and significant effect of the work environment on lecturer performance, work environment on work motivation, work motivation on lecturer performance, work environment on job satisfaction. However, job satisfaction has no significant effect on lecturer's performance. The result of mediation testing, work motivation mediate the effect of the work environment partially to lecturer performance, and job satisfaction hasn't a role as a mediation on the effect of the work environment to lecturer performance.